Good Governance Alokasi Dana Desa (ADD): Peran Perangkat dan Akuntabilitas Publik - Desi Susilawati; Parwoto Parwoto; Puspita Dewi Wulaningrum; Tri Tri Wijayanto (Journal of Applied Accounting and Taxation, 2020)
This research was conducted related to the accountability of the management of the Village Fund Allocation (ADD) 2018 in Village of Tirtomartani, Kalasan District. The research objectives are 1) Measuring the Role of Village Apparatuses in realizing good governance in managing village financial funds, 2) to determine the accountability of ADD management can work effectively for all dimensions, namely Transparency, Accountability and Participation in each process and stage which includes the Planning Phase, Implementation and Reporting 3) to help resolve the problems in the management of ADD so that issues regarding the management of ADD can prove and explain the strategic plans and objectives or the goals that have been planned and established by village government organizations through the meeting mechanism of village development planning. The results of this research that the principle of transparency and participation had been implemented well through the mechanism of consultation and deliberation that involved all elements of village community institutions, indicated by the answers of respondents show 91% answered "yes". The principle of transparency is fulfilled by the existence of clear information about the schedule of implementation of activities, sources of funds that are easily accessed by the community, showed that respondents' answers“yes” were 85.6%, which meant that implementation the ADD APBDES was already accountable. Although ADD management has been accountable, it certainly cannot be separated from the role of village officials or village apparatus which is a key to the successful management of ADD APBDES. The results showed that the role of village apparatus in Tirtomartani village was 72%., indicated that village apparatus have played a role to create good governance of managing ADD. This research is expected to contribute in the form of Transfer of Knowledge for village government administrators in order to be optimalized in the management of ADD in the planning process, implementation (expenditure of funds) and reporting in accordance with the provisions of the central government.